Factors associated with implemented teacher-led movement and physical activity in early childhood education and care - Sollerhed, Ann-Christin (Frontiers in Psychology, 2023)
This study aimed to explore early childhood education and care (ECEC) educators' reported frequency of implemented gross motor and physical activities (MoPA) among children in ECEC, as well as the educators' reported personal physical activity PA levels in leisure time. A cross-sectional survey was performed in 68 preschools in southern Sweden. Data were obtained from questionnaires completed by 359 ECEC educators. The participation rate was 61 %. About two thirds offered MoPA once a week or more seldom, while one quarter offered MoPA at least every other day. Educators who reported personal PA three times or more per week, offered MoPA for the children at least every other day to a higher extent (37%) compared to colleagues who reported personal PA once or twice a week (26%) or colleagues who reported that they were never or seldom active (18%) (p=0.034). The results from multiple logistic regression analysis showed that reported implemented MoPA among children in ECEC was significantly associated with the educators' perceptions that free play improved children's gross motor skills (OR 2.7), the educators' perceptions of needed curricular guidelines for MoPA (OR 2.1), the educators' own leisure PA level (OR 2.0) and the educators' perceptions that adequate gross motor skills were not learned at home (OR 0.4). Teacher-led MoPA occurs sparingly during the preschool day and the teachers believe that the children get sufficient PA in free play. The children are expected to develop their motor skills to a sufficient extent during the short moments of offered outdoor play. Teachers who are physically active in their leisure-time seem to offer gross motor training for the children to a higher extent than less active or inactive colleagues.